2016
DOI: 10.1590/0103-8478cr20151600
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Erwinia psidii in guava plants under greenhouse and field conditions

Abstract: Erwinia psidii causes bacterial blight of guava (Psidium guajava), an important disease of this crop in Brazil. The pathogen affects branches and twigs of guava trees, reducing yield significantly. Bacterial dissemination often occurs through

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…juglandis -specific primer. DNA quantities are expected to be low in the wood shaving samples because the DNA would have come from molted exoskeletal structures or frass from the beetles [ 26 ]. Another possible explanation for the low detection rate of P .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…juglandis -specific primer. DNA quantities are expected to be low in the wood shaving samples because the DNA would have come from molted exoskeletal structures or frass from the beetles [ 26 ]. Another possible explanation for the low detection rate of P .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular techniques can provide valuable tools in plant disease diagnosis and can be used for the simultaneous detection and identification of plant pathogens [ 26 ]. PCR-based methods have become the primary means for the early detection of pathogens in agriculture and forestry [ 27 ], as well as in human and animal health [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. psidii can be disseminated by asymptomatic propagating plant material. Development of efficient methods to detect the pathogen in symptomatic and asymptomatic plant material has been the subject of several studies (Teixeira et al 2008;Silva et al 2015;Silva et al 2016). Bio-PCR, a variation of PCR that employs an enrichment step prior to DNA amplification (Schaad et al 1995) has been shown to be suitable for early disease diagnosis in guava orchards (Silva et al 2016).…”
mentioning
confidence: 99%
“…Several studies have focused on developing methods for inoculation on guava and eucalyptus (Marques et al 2007;Ferraz et al 2016), methods for disease diagnosis (Teixeira et al 2008;Silva et al 2015;Silva et al 2016), and assessment of pathogen diversity (Teixeira et al 2009). However, very Section Editor: Rodrigo Almeida Electronic supplementary material The online version of this article (https://doi.org/10.1007/s40858-018-0236-y) contains supplementary material, which is available to authorized users.…”
mentioning
confidence: 99%